Hakikat Membaca di Kelas Tinggi di Tingkat SD/MI - Adha Zam-Zam Hariro; Annida Azhari Ritonga; Friska Widia; Juni Sahla Nasution (Badan Penerbit STIEPARI Press, 2024)
In the world of education, reading skills are very fundamental. Apart from all learning processes that are based on reading and writing activities, reading proficiency is a stepping stone for every person's success, both in the school context and in life in society. This research aims to find out more about the nature of reading in higher grades at the SD/MI level. The method used in this research is a qualitative method based on literature analysis studies. Reading is the ability to use thoughts and actions to carry out visual activities by pronouncing a series of letters into words and sentences, mastering reading techniques and understanding the content of the reading correctly. The aim of reading in higher grades is to develop critical and creative reading skills. Students are not only required to capture information, but also analyze, assess and use information. Based on the research results, it can be concluded that understanding the nature of reading in higher grades has a great influence on students' understanding of advanced reading.